La promoción y protección de la libre competencia en la ley 142 de 1994 (2014)
This article presents an analysis of the Law 142 of 1994 as a mechanism for the promotion and protection of competition in order to protect the economic freedom of users. To support this idea different aspects of the constitutional and legal system are reviewed as well as the role of competition in the provision discussion of household public services, insofar as it means a theoretical challenge to the Colombian legal system. It is suggested to differentiate the concept of competition with the idea of introduction of neoliberalism in the provision of these services